Complex disease dynamics and the design of influenza vaccination programs. - Steven Riley (PLoS Medicine)
Reflecting on new research by Cécile Viboud and colleagues, Steven Riley describes how understanding complex influenza dynamics can aid the design of influenza programs in China. Please see later in the article for the Editors' Summary.